Genomic sequencing of a frog virus 3 strain from cultured American bullfrogs (Lithobates catesbeianus) in Brazil - Ferreira, Claudia Maris; Subramaniam, Kuttichantran; de Sousa, Ricardo Luiz Moro; Tavares, Loiane S.; Corrêa, Thaís C.; Waltzek, Thomas B. (Archives of virology, 2021)
Frog virus 3 (FV3) was detected in cultured bullfrogs in Southeast Brazil. Phylodynamic analysis revealed recombination events in this strain that were nearly identical to those detected in North American and Brazilian FV3 strains. These data suggest that international trade of live bullfrogs has spread recombinant strains of FV3.